Can small stores have a big impact? A qualitative evaluation of a store fruit and vegetable initiative. (19th December 2013) - Gardiner, Breeana; Blake, Miranda; Harris, Raeleigh; Gee, Carena; Charaktis, Stella; Choong, Christine; Lade, Rebecca; Duff, Laura; Palermo, Claire
Abstract : Issue addressed: The aim of this evaluation was to explore the quality, barriers, enablers and outcomes of a retail fresh fruit and vegetable initiative in rural communities identified to have poor geographic access to healthy food. Methods: A qualitative evaluation using in‐depth interviews was conducted with rural store retailers across Victoria involved in the implementation of a retail fruit and vegetable initiative. Data were analysed using a thematic approach. Results: Six of the 13 store retailers that were engaged in the initiative identified a range of qualities, barriers, enablers and outcomes. They reported that effective communication is essential for engaging retailers and sustaining participation. The choice and use of retail incentives may influence the community's purchase of fruit and vegetables. The community's attitude to fruit and vegetables, the staff's ability to promote produce and the capacity of the store to stock and sell fresh fruit and vegetables influenced perceived success. Barriers included difficulties receiving a regular supply of fresh fruit and vegetables, time constraints and storage facilities. Conclusions: This qualitative evaluation of a retail fruit and vegetable initiative found that effective leadership and communication from project workers, a range of retail incentives and the capacity of the store to promote, stock and sell fresh fruit and vegetables influenced perceived success. So what?: Fruit and vegetable retail initiatives in small rural community stores may have a role in supporting consumption of fruit and vegetables. Abstract : The aim of this evaluation was to explore the quality, barriers, enablers and outcomes of a retail fresh fruit and vegetable initiative in rural communities identified to have poor geographic access to healthy food. It was found that effective leadership and communication from project workers, a range of retail incentives and the capacity of the store to promote, stock and sell fresh fruit and vegetables influenced perceived success. Fruit and vegetable retail initiatives in small rural community stores may have a role in supporting consumption of fruit and vegetables.